Hypophyseal Involvement in Immunoglobulin G4-Related Disease: A Retrospective Study from a Single Tertiary Center - Yang Liu; Linjie Wang; Wen Zhang; Hui Pan; Hongbo Yang; Kan Deng; Lin Lu; Yong Yao; Shi Chen; Xiaofeng Chai; Feng Feng; Hui You; et al. (International Journal of Endocrinology)
This study aims to outline the clinical features and outcomes of IgG4-related hypophysitis (IgG4-RH) patients in a tertiary medical center. We reviewed clinical manifestations and imaging and pituitary function tests at baseline, as well as during follow-up. Ten patients were included. The mean age at diagnosis of IgG4-RH was 48.4 (16.0–64.0) years. An average of 3 (0–9) extrapituitary organs were involved. Five patients had panhypopituitarism, three had only posterior hypopituitarism, one had only anterior hypopituitarism, and one had a normal pituitary function. One patient in our study had pituitary mass biopsy, lacking IgG4-positive cells despite lymphocyte infiltration forming an inflammatory pseudotumor. Five patients with a clinical course of IgG4-RH less than nine months and a whole course of IgG4-RD less than two years were managed with glucocorticoids, while three patients with a longer history were administered glucocorticoids plus immunosuppressive agents. One patient went through surgical excision, and one patient was lost to follow-up. All patients showed a prompt response clinically, but only three patients had normalized serum IgG4 levels. Two patients who took medications for less than six months relapsed. Conclusions. IgG4-RD is a broad disease, and all physicians involved have to be aware of the possibility of pituitary dysfunction. Younger patients should be expected. The histopathological feature of pituitary gland biopsy could be atypical. For patients with a longer history, the combination of GC and immunosuppressive agents is favorable. Early and adequate courses of treatment are crucial for the management of IgG4-RH. With GC and/or immunosuppressant treatment, however, pituitary function or diabetes insipidus did not improve considerably.